Modifikasi Perilaku Dalam Mengatasi Perilaku Phobia Terhadap Kegelapan (Nyctophobia) Pada Anak Usia Dini - Indah Sa'adah; Ari Purnomo Endah Aflahani (JURNAL LENTERA ANAK, 2022)
This study aims to determine the effectiveness of behavior modification programs in overcoming dark phobic behavior or commonly known as Nyctophobia in early childhood using flooding methods and systemic desensititation. This research uses a qualitative approach with a single case study method. The data collectoin techniques used assessment, interview, and observation. Subjects in this study amounted to one person, aged 6 years 3 months, and experiencing phobia conditions. The results showed that the behavior modification program using flooding methods and systemic desensititation to overcome phobic behavior, can reduce the level of phobic anxiety against darkness but has not been maximally successful. Until now, the subject sometimes still has difficulty overcoming excessive anxiety against dark phobia. Where this happens because there are still excessive traumatic and hallucinations experienced by the subject.